Before Microfinance: The Social Value of Microsavings in Vincentian Poverty Reduction - Tavanti, Marco (2013)
The purpose of this article is to present and discuss the values and limits of microfinance within the context of poverty reduction, international development, and community empowerment. The main thesis is that microfinance requires a more complex strategy than simply the provision of credits. The development of financial capital depends on the increase in human capacity and social capital. Microfinance is revisited under the ethical lenses of global responsibility for alleviating poverty and developing community sustainability. Through a critical review of the literature and case studies from the Philippines, the author suggests a value-based Vincentian approach to integrate microfinance into community empowerment. In connection with the main thesis the author argues that the achievement of economic self-reliance through microfinance is contingent upon the development of capacity building, social capital, and empowerment at the individual, collective, and systemic levels.
Keywords: Vincentian; Sustainable community development; Self-reliance; Philippines; MFIs; Microsavings; Microfinance; Microcredit